A phase 1 trial extension to assess immunologic efficacy and safety of prime-boost vaccination with VXM01, an oral T cell vaccine against VEGFR2, in patients with advanced pancreatic cancer. (3rd April 2018) - Schmitz-Winnenthal, Friedrich H.; Hohmann, Nicolas; Schmidt, Thomas; Podola, Lilli; Friedrich, Tobias; Lubenau, Heinz; Springer, Marco; Wieckowski, Sébastien; Breiner, Klaus M.; Mikus, Gerd; Büchler, Markus W.; Keller, Anne-Valerie; et al.
ABSTRACT: VXM01 is a first-in-kind orally applied tumor vaccine based on live attenuated Salmonella typhi carrying an expression plasmid encoding VEGFR2, an antigen expressed on tumor vasculature and a stable and accessible target for anti-angiogenic intervention. A recent randomized, placebo-controlled, phase I dose-escalation trial in advanced pancreatic cancer patients demonstrated safety, immunogenicity and transient, T-cell response-related anti-angiogenic activity of four priming vaccinations applied within one week. We here evaluated whether monthly boost vaccinations are safe and can sustain increased frequencies of vaccine-specific T cells. Patients with advanced pancreatic cancer were randomly assigned at a ratio of 2:1 to priming with VXM01 followed by up to six monthly boost vaccinations, or placebo treatment. Vaccinations were applied orally at two alternative doses of either 10 6 colony-forming units (CFU) or 10 7 CFU, and concomitant treatment with standard-of-care gemcitabine during the priming phase, and any treatment thereafter, was allowed in the study. Immunomonitoring involved interferon-gamma (IFNγ) ELIspot analysis with long overlapping peptides spanning the entire VEGFR2 sequence. A total of 26 patients were treated. Treatment-related adverse events preferentially associated with VXM01 were decreases in lymphocyte numbers in the blood, increased frequencies of neutrophils and diarrhea. Eight out of 16 patients who received at least one boosting vaccination responded with pronounced, i.e. at least 3-fold, increase in VEGFR2-specific T cell response over baseline levels. In the VXM01 vaccination group, VEGFR2-specific T cells peaked preferentially during the boosting phase with an average 4-fold increase over baseline levels. In conclusion, prime/boost vaccination with VXM01 was safe and immunogenic and increased vaccine specific T cell responses compared with placebo treatment.